Kepemimpinan dan Kerja Sama untuk Meraih Mutu Pendidikan: (Re-aktualisasi Peran Sumber Daya Manusia melalui Total Quality Management dalam Manajemen Pendidikan Islam) - Musayyidi Musayyidi; Hafid; Matlani (Institut Kariman Wirayudha Sumenep, 2024)
There are four basic efforts that must be made in a product/service producing institution to produc better quality, in this case an islamic educational institution, namely : (1) Creating a “win win” situation an not “win win” situation. “lose win” between parties with an interest in product / service producing institutions (stakehoulders). In this case, especially between the leadhership / owner of the institution and the staff of the institution, there must be mutually beneficial conditions for each other in achieving thue quality of the products / service produced by the institutions (2) it is necessary to develop instrinsic motivation in everyone involved in the process of achieving product / service quality. Every person must grow motivated that the result of their activites reach a certain quality that continues to improve, especially in accordance with the needs and expectations of user / subcribbes. (3) every leader must be oriented towards long-term process and results. Impelementing TQM is not a short-term change process, but a consistent and continous log-term effort (4) in mobilizing all institutional capabilities to achieve the specified quality, cooperation must be developed be results. There should be no competion between them that interferes with the process of achieving quality results they are a unit that must work together and cannot be separated from each other to produce quality products / services as expected.